Cranial Ultrasound in the Management of Hydrocephalus in Newborns: A Case Series - Bogdan Florin Gonț; Loredana Mitran; Vlad Dima; Simona Vlădăreanu (Children)
Background: Hydrocephalus in preterm and term newborns is a condition with an important impact on medical care and the neurological development of patients, with high expenditures regarding daily care. Imaging nowadays provides valuable information regarding the aetiology of the condition, and it represents a great aid in monitoring the development of the patients. Materials and methods: In this article, we present the cases of five patients with hydrocephalus, for which different imaging methods were used to detect and treat the underlying aetiology, emphasizing the cranial ultrasound examination. Results: The results provided valuable information regarding the utility and feasibility of ultrasound. Moreover, Prechtl’s Assessment of General Movements is yet another useful tool, which in correlation with the use of cranial ultrasound can provide good insight regarding the evolution of the affected newborns. The Kurjak Antenatal Neurodevelopmental Test (KANET, KANE Test) comes in handy in the case of prenatal neurological assessments. Conclusions: Ultrasound examination proves to be a worthy tool capable of detecting the aetiology; however, in several cases, a complementary imaging examination might be needed. The therapeutic approach should take into consideration the diverse aetiology of the disease.